Pandangan Al-Qur’an Dan Hadist Terhadap Etos Kerja - Nurdin, Fauziah (Forum Intelektual Qur'an dan Hadits Asia Tenggara (SEARFIQH) Kota Banda Aceh, 2020)
Alquran and Hadits are Islamic teachings in which there are teachings for charity and work which are recited in the sentence